KINERJA MANAJERIAL PEMERINTAH DESA ARGAPURA MELALUI PARTISIPASI PENYUSUNAN ANGGARAN DAN KEJELASAN SASARAN ANGGARAN - Rahmayani, Melia Wida; Kurnadi, Engkun; Riyadi, Wulan; Hernita, Nita; Gumilang Lestari, Ayu (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Managerial performance is very important for the survival of organizations, especially government organizations because it is the result of the organization's work in carrying out community service activities. Efforts to improve managerial performance through Participation in Budgeting and Clarity of Budget Targets. The purpose of this study is to determine the extent to which Participation in Budgeting and Clarity of Budget Targets Affects the Managerial Performance of the Argapura Village Government. The method used is descriptive verification in which the researcher describes the state of budgetary participation, clarity of budget targets and managerial performance of the village government of Argapura. The analysis used in this study uses partial hypothesis testing, multiple linear regression analysis, and analysis of the coefficient of determination. The results of this study have a significant effect between variables